Fine Needle Aspiration Cytology of Malignant Digestive System Gastrointestinal Neuroectodermal Tumor in a Lymph Node Metastasis from a Previously Diagnosed Liver Primary: A Case Report and Review of Literature. Issue 3 (25th September 2020) - Gadde, Ramya; Linos, Konstantinos; Lisovsky, Mikhail; Kerrigan, Timothy; Loehrer, Andrew P.; Kasumova, Gyulnara; Kerr, Darcy A.; Liu, Xiaoying
Abstract: Malignant gastrointestinal neuroectodermal tumor (GNET) is an extremely rare neoplasm. Immunohistochemically, GNET typically demonstrates neural differentiation but lacks melanocytic differentiation, making it distinct from clear cell sarcoma of the soft tissues (CCS). Herein we report for the first time the cytomorphologic features of lymph node metastasis from presumably liver GNET. A 36‐year‐old female presented with fevers, night sweats, loss of appetite, and a 20‐lbs weight loss. Radiographic imaging showed a 13 cm heterogeneously enhancing mass in the right lobe of the liver and a hypermetabolic 0.9 cm periportal lymph node on positron emission tomography–computed tomography (PET/CT). Initially, a CT‐guided liver biopsy was performed followed by right hepatic lobectomy and portal lymphadenectomy. The liver biopsy and resection showed an S100‐protein and SOX10 positive malignant neoplasm and genomic profiling of liver biopsy revealed EWSR1‐CREB1 gene rearrangement. These findings in conjunction with the morphologic and immunohistochemical profile were diagnostic of GNET. Two months later, she presented with recurrent lymphadenopathy in the upper abdomen. Fine needle aspiration of the periportal nodal mass revealed single and clusters of primitive, large to medium‐sized neoplastic cells with round to oval nuclei, high nuclear‐cytoplasmic ratio, vesicular chromatin, and prominent nucleoli. The tumor cells were S100 protein and SOX10 positive, consistent with metastasis of the patient's recently diagnosed malignant digestive system GNET. Palliative chemotherapy was administered but the patient died a few days later, 4 months from the initial diagnosis. Awareness of this entity and judicial use of ancillary studies including molecular testing are essential for achieving accurate diagnosis.